A Family of High‐Efficiency Hydrogen‐Generation Catalysts Based on Ammonium Species1. (18th June 2015) - Lu, Lilin; Zhang, Haijun; Zhang, Shaowei; Li, Faliang
Abstract Development of highly active, low cost, ecologically friendly, and durable homogenous catalysts for hydrogen generation from hydrolysis of borohydride is one of the most desirable pathways for future hydrogen utilization. The unexpected catalytic activities of inorganic ammonium species and the corresponding mechanisms underpinning them are studied. The catalytic activities of the ammonium species are higher than or comparable to those of mostly investigated noble‐metal/transition‐metal catalysts (such as Pd, Pt, Ni, and Co) but are considerably cheaper, more environmentally friendly, and more readily available. Quantum chemical calculations indicate that the unique ammonium‐induced reaction pathway involved with a barrierless elementary reaction at the reaction entrance and the formation of the highly active intermediate BH3 are responsible for the unexpected catalytic activities and the significantly accelerated hydrogen generation.